DISKRIPSI PENYEBAB KEMISKINAN DI KELURAHAN BANJAR SERASAN KECAMATAN PONTIANAK TIMUR - B21110023, Zimri (Jurnal Pembangunan dan Pemerataan, 2015)
To the effect of observational is subject to be know society poverty cause at serasan's Line sub-district Pontianak's district East. Method that is utilized is descriptive method with primary data and secondary data. Base observational result gets to be known that poverty causal factor at serasan's Line which is: low income, low education and low productivity.Â  There is program even that done by pemerintahuntuk can help society to reduce poverty number or to petrify soften indigent society cost of living which is indigent rice program (Raskin), health surety program (jamkesmas). Prpgram is expectation family (PKH) and indigent student help program (BSM), But that program ekfektif's reducing, karean by marks sense that program msikin's society on the contrary gets lazy bekrjaan or tries for labih well. Base observational result and study already being done therefore gets to be gleaned from from poverty cause at Pontianak's district East which is: Its low is propertied respondent perhari so they can't meet the need knockabout life, Its low is level health because of no society consciousness to look after their vicinity environment even discard waste behind house, Its low is productivity is measured from sleep build, the time of day job going, until goes home job, since they can't do some part to result income therefore they don't take down from poverty. keywords: Income, Education, And Productivity. Â